2018
DOI: 10.1136/bjophthalmol-2018-312643
|View full text |Cite
|
Sign up to set email alerts
|

Choriocapillaris impairment around the atrophic lesions in patients with geographic atrophy: a swept-source optical coherence tomography angiography study

Abstract: A significant impairment of the CC flow is present in the zone immediately surrounding the GA lesions strengthening the hypothesis that CC alterations may be relevant to the progression of GA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 37 publications
6
58
0
Order By: Relevance
“…Regardless, these regional differences in the CC that are accentuated by age must be taken into account in any studies comparing potential CC abnormalities in different parts of the macula. To address these regional differences, in a recent study evaluating CC flow deficits surround geographic atrophy lesions,[ 16 ] we compared regions at equal distances from the foveal center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless, these regional differences in the CC that are accentuated by age must be taken into account in any studies comparing potential CC abnormalities in different parts of the macula. To address these regional differences, in a recent study evaluating CC flow deficits surround geographic atrophy lesions,[ 16 ] we compared regions at equal distances from the foveal center.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by histologic studies which have demonstrated differences in the CC morphology in central compared to more peripheral regions [ 2 ]. These topographical variations in the CC may be significant confounders of studies which compare CC flow deficits within regions of interest in the macula [ 3 , 4 , 15 , 16 ]. To study the potential impact of these regional and age-related variations, we studied the topographical distribution of CC flow deficits in a cohort of normal subjects.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 3 , 4 Recent optical coherence tomography angiography (OCTA) studies have shown that eyes with geographic atrophy exhibit greater CC flow deficits (FD) versus normal eyes and versus eyes with neovascular AMD and that CC impairment may predict the progression of geographic atrophy (GA). 5 7 …”
mentioning
confidence: 99%
“…With rare exception, there is an increase in both flow deficit metrics from the early stage through the advanced stage. This might be expected based on OCTA and histology studies that have found flow or vessel impairment beneath drusen and around GA lesions 17,[19][20][21][22] and progressively by dry AMD stage. 12,23 Even if stage is minimally contributory to flow deficit metrics, this trend is consistent with the findings of multiple studies of age in the CC, [7][8][9][10][11][12] as there was a respective increase in the mean ages of early, intermediate, and advanced eyes in our cohort (early, intermediate, and advanced eye mean ages: 72, 77, and 81 years, respectively).…”
Section: A Casementioning
confidence: 68%